Perfil de ácidos graxos e análise sensorial de carne e iogurte de leite de caprinos alimentados com óleos vegetais - Dibbern, Lucas Schimidt [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Foods with lower fat and or better fatty acid profile are the main focus of the market for animal products. Therefore, this study aimed to evaluate the inclusion of three vegetable oil sources in the diet of lactating goats on the composition, fatty acid profile and sensory parameters of yogurt made from milk of these goats. Were used 32 Anglo-Nubian goats distributed in four treatments: control diet versus with inclusion of 3% of canola, sunflower and soybean oil. The influences of treatments and lactation periods on the composition, fatty acid profile and sensory parameters of the yoghurt were evaluated. For determination of the constituents, samples were taken at 21, 51, 81 and 111 days of lactation and the profile of fatty acids at 21 and 111 days of lactation. Milk production in 120 days of lactation was 182.75 kg and there is no difference to the treatments. The constituents were not affected by the treatments, but difference on the protein content was seen at period. For fat and defated dry extract was interaction between treatment and period. The inclusion of sunflower and soybean oils promoted an increase in the total content of polyunsaturated fatty acids (PUFA) and conjugated linoleic acid (CLA). The index of atherogenicity (IA) improved with the addition of oil in the diet of animals, being more pronounced in the treatments with sunflower and soybean oil. For sensory analysis of the yogurt the treatments including sunflower oil and soybean showed no difference from the control treatment (no addition of oil) for taste parameter but yogurt of the treatment with canola oil showed a difference. For consistency all treatments with the addition of oil were different from the control treatment, still yogurt from the treatment with canola oil the less accurate than the control. These results suggest that the addition of 3% of vegetable oils in the diet of lactating goats improves ...

Alimentos com menores teores de gordura e ou com melhor perfil de ácidos graxos são o principal enfoque do mercado para produtos de origem animal. Portanto, este trabalho objetivou avaliar a inclusão de três fontes de óleo vegetal na dieta de cabras em lactação sobre a composição, o perfil de ácidos graxos e os parâmetros sensoriais do iogurte produzido com o leite destas cabras. Foram utilizadas 32 cabras da raça Anglo-nubiana distribuídas em quatro tratamentos: dieta controle versus com inclusão de 3% de óleos de canola, girassol e soja. Foram avaliadas as influências de tratamentos e períodos de lactação sobre a composição, o perfil de ácidos graxos e os parâmetros sensoriais do iogurte. Para determinação dos constituintes, foram colhidas amostras aos 21, 51, 81 e 111 dias de lactação e para o perfil de ácidos graxos aos 21 e 111 dias de lactação. A produção leiteira em 120 dias de lactação foi de 182,75 kg e não houve diferença para os tratamentos. Os constituintes, não foram influenciados pelos tratamentos, entretanto o teor de proteína apresentou efeito para período. Para gordura e extrato seco desengordurado houve interação entre tratamento e período. A inclusão de óleos de girassol e soja promoveu aumento no teor total de ácidos graxos poli-insaturados (AGPI) e de ácido linoléico conjugado (CLA). O índice de aterogenicidade (IA) melhorou com a adição de óleo na dieta dos animais, sendo mais acentuada nos tratamentos com óleo de girassol e soja. Para a análise sensorial os iogurtes dos tratamentos com inclusão de óleos de girassol e soja não apresentaram diferença do tratamento controle (sem adição de óleo) para o parâmetro sabor, já o iogurte do tratamento com óleo de canola demonstrou diferença. Para a consistência todos os tratamentos com adição de óleo foram diferentes do tratamento controle, sendo ainda o iogurte ...
Keywords: Caprino - Alimentação e rações; Leite de cabra; Iogurte; Carne - Qualidade; Óleos vegetais; Dieta em veterinaria; Alimentos funcionais; Acidos graxos; Alimentos - Avaliação sensorial; Goats - Feeding and feeds